2014
DOI: 10.2527/jas.2013-7494
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of three methods of temperament evaluation of Brahman calves 1

Abstract: The objective of this study was to estimate the heritability of 3 measures of temperament in Brahman and Brahman-influenced calves (n = 1,209). Individual animal pen scores (PS) were determined by a trained observer who evaluated groups of 5 or 4 calves at a time for willingness to be approached by a human. Exit velocity (EV) was the rate (m/s) at which each calf exited a squeeze chute. Temperament score (TS) was calculated individually as (PS + EV)/2. Temperament was evaluated at 5 different times of record (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
1
20
2
Order By: Relevance
“…Increases in weight (weaning weight from approximately 2 mo earlier; weights were not recorded at the time of temperament scoring) were associated with reductions in all temperament scores. This is consistent with regressions of exit velocity or subjective chute scores in heifers after weaning (Elzo et al, 2009;Riley et al, 2010); however, in young calves there may be a positive regression on weight until a certain age, after which increases in weight are again associated with decreases in exit velocity and other evaluations of temperament (Schmidt et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Increases in weight (weaning weight from approximately 2 mo earlier; weights were not recorded at the time of temperament scoring) were associated with reductions in all temperament scores. This is consistent with regressions of exit velocity or subjective chute scores in heifers after weaning (Elzo et al, 2009;Riley et al, 2010); however, in young calves there may be a positive regression on weight until a certain age, after which increases in weight are again associated with decreases in exit velocity and other evaluations of temperament (Schmidt et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…; Schmidt et al . ). Higher heritabilities for temperament traits were also found in German Angus (ranged from 0.0 to 0.61) and Simmental cattle (ranged from 0.0 to 0.59) (Gauly et al .…”
Section: Discussionmentioning
confidence: 97%
“…Even though, some references could be found for cattle temperament traits with heritability values ranging from low to high. For example, for those cattle breeds mainly selected for docility like the Limousin or Brahman breeds, the heritability value estimates ranged from 0.11 to 0.49 (Benhajali et al 2010;Schmidt et al 2014). Higher heritabilities for temperament traits were also found in German Angus (ranged from 0.0 to 0.61) and Simmental cattle (ranged from 0.0 to 0.59) (Gauly et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Results of Pearson's correlation coefficient in this study were inconsistent with those described in other studies focused on correlating temperament with growth, because all the correlations found here were positive. This finding could be related to the time at which temperament was recorded (Curley et al, 2006;Schmidt et al, 2014). Temperament of animals is usually recorded around weaning time, either pre-or post-weaning.…”
Section: Discussionmentioning
confidence: 99%